The Gendered Dimension of Crime: An Analysis of Female Criminality - Halima MENANI (Management Intercultural)
This article focuses on the notable increase in female criminality, which has generated special interest in criminology because it is a less common phenomenon than that of men. Analysis of female crime progressed beyond Lombroso’s early biological determinism. Recent studies show women are less frequently involved in serious crime compared to men, a difference that societal expectations of women may explain. Their social status and the choices available to them usually shaped women’s criminal behavior. Underlying this, however, is a less visible, less examined type of crime. Societal factors heavily influence the kinds of crimes women are involved in. This situation led to the development of specific theories about female crime, distinguishing itself from classical explanatory models focused on male crime. This theoretical progress contributed to a critical movement that challenged conventional methodologies, particularly through radical movements that emphasized the need to consider structural and societal aspects to understand female criminality.